Juridical Analysis of the Binding of Inherited Land that has not been Divided as the Object of Debt Collateral (Case Study of the Decision of the Supreme Court of the Republic of Indonesia Number 2189 K / PDT / 2017) - Rika Devi Yanti Nasution; Yamin Lubis; Mustamam Mustamam (LEGAL BRIEF, 2020)
DOI: https://doi.org/10.35335/Legal.Vol9i2 The parties in the loan or credit agreement, bind the inherited land that has not been divided as a debt collateral object, namely by guaranteeing inherited land that has not been distributed to the heirs. The formulation of the problem in this thesis is how the position of inherited land which is used as collateral originating from the sale and purchase of land from an heir, how the legal consequences of the sale and purchase of inheritance land are used as collateral in the loan receivables agreement, how is the judge's judgment in deciding the Supreme Court Decision Number 2189 K / Pdt / 2017 if seen from the guarantee law. The research method used is descriptive analysis that leads to normative juridical research that is research conducted by referring to legal norms that is examining library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results showed that the position of inherited land that is used as collateral originating from the sale and purchase of land from an heir is that there must be an agreement of the heirs to avoid the seizure of inheritance between heirs, who appear with the desire to own most or all of the inherited assets that are inherited. Abandoned, registration of transfer of mortgage rights is carried out by recording it in the land book and certificate of related mortgage rights and in the land book and certificate of rights encumbered based on a letter of evidence of the transfer of receivables guaranteed due to inheritance. The transfer of land rights due to inheritance is not one of the causes of the abolition of the Underwriting Right, therefore the Underwriting Right will not be abolished by the transfer of land rights that it encumbered. Judge's consideration in deciding the Republic of Indonesia's Supreme Court Decision Number 2189 K / Pdt / 2017 if seen from the guarantee law is land that has been the object of collateral for a credit loan legally. The guarantee cannot be transferred or sold or carried out a legal action on the object of the guarantee without the permission of other heirs as well as creditors namely the North Sumatra Bank as the party entitled to the guarantee.